1989
DOI: 10.1128/mcb.9.1.204
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of autocrine stimulation in hematopoietic cells producing interleukin-3 after retrovirus-mediated gene transfer.

Abstract: Endogenous expression of the interleukin-3 (IL3) gene introduced with a retrovirus vector renders hematopoietic cells autonomous of exogenous growth factor. To investigate the mechanism of autocrine stimulation, 25 clones were isolated after retrovirus transduction of IL3 into 32D-c123 or FDC-P1 cells. Medium conditioned by these autonomous IL3-producing clones supported the growth of factor-dependent 32D cells. Although there was a severalfold variation in the amount of IL3 secreted (some clones secreted bare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0
1

Year Published

1989
1989
2001
2001

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 28 publications
6
20
0
1
Order By: Relevance
“…Analogous results have been obtained with the murine IL-3 gene (14,15,38). In some cases, autonomous growth appeared to depend on secretion of the growth factor (14,15,18), whereas cell proliferation of other growth factor-producing lines was insensitive to cell density and neutralizing antibody (6,20).…”
supporting
confidence: 59%
“…Analogous results have been obtained with the murine IL-3 gene (14,15,38). In some cases, autonomous growth appeared to depend on secretion of the growth factor (14,15,18), whereas cell proliferation of other growth factor-producing lines was insensitive to cell density and neutralizing antibody (6,20).…”
supporting
confidence: 59%
“…Work by Browder et al [12) is in accordance with this hypothesis. Infection of multi-CSF-dependent 32D cells with a construct encoding a modified multi-CSF protein that does not direct the CSF molecule into the ER for processing did not lead to factor independence, although the gene product localized in the cytosol proved to be biologically active.…”
Section: F Summary and Conclusionsupporting
confidence: 81%
“…Analysis of leukemic cells from both AML and CML patients have provided evidence in support of the hypothesis that aberrant expression of growth factor genes (e.g., GM-CSF and G-CSF) may contribute to the uncontrolled growth of the leukemic cells [13,14]. Indeed, two experimental studies have demonstrated the causal correlation of aberrant factor production with leukemogenic growth: unregulated expression of an IL-6 gene conjugated to the human Ig heavy chain gene enhancer (E~) in transgenic mice triggers generation of plasmacytoma/myeloma (Suematsu and Kishimoto, cited in [15]) and expression of IL-3 in a retroviral construct introduced in vivo via murine hematopoietic stem cells leads to a hematopoietic disorder similar to CML [12].…”
Section: G Outlookmentioning
confidence: 99%
“…In addition, the blocking ofthis response by IL-6 antisense oligonucleotide, but not by anti-IL-6 neutralizing mAb, suggests that it is mediated by IL-6 in an intracytoplasmic mechanism. This is analogous to previous reports of autocrine systems wherein cell growth is insensitive to exogenous growth factors and neutralizing antibodies are unable to inhibit proliferation (45)(46)(47)(48)(49). Such systems are compatible with a mechanism whereby receptor association and signal transduction both occur internally.…”
Section: Resultssupporting
confidence: 63%